The sale of antibiotics without prescription in pharmacies in Damascus, Syria - Zaid Al-Faham; Ghaith Habboub; Farah Takriti (Journal of Infection in Developing Countries)
Introduction: Overuse of antibiotics has contributed to the development of organism resistance. The acquisition of antibiotics without prescription by the general population seems to be common practice in pharmacies of Damascus, Syria. This study aimed to determine the proportion of pharmacies dispensing antibiotics without medical prescription and without seeing the patient.